2009
DOI: 10.1063/1.3224125
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved specular and off-specular neutron reflectivity measurements on deuterated polystyrene and poly(vinyl methyl ether) blend thin films during dewetting process

Abstract: We performed time-resolved specular and off-specular neutron reflectivity measurements on blend thin films 42 and 98 nm thick of deuterated polystyrene and poly͑vinyl methyl ether͒ during dewetting process induced by the phase separation in two phase region using a time-of-flight neutron reflectometer. In the specular measurements we found that the phase separation directed to the depth direction occurred near the air interface as well as near the Si substrate during the incubation period before dewetting. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The kinetics during the dewetting process of blend thin films deuterated polystyrene and poly vinyl methyl ether was studied by time-resolved specular and OFFSpec NR measurements. It is reported that the droplets formation on the micrometer length scale occurs in the late stage of dewetting [41]. As indicated above the self assembly of three block polymer micelles at solid interfaces is a good showcase for GIS from solid-liquid boundaries and a range of molecules has been investigated.…”
Section: Examplesmentioning
confidence: 94%
“…The kinetics during the dewetting process of blend thin films deuterated polystyrene and poly vinyl methyl ether was studied by time-resolved specular and OFFSpec NR measurements. It is reported that the droplets formation on the micrometer length scale occurs in the late stage of dewetting [41]. As indicated above the self assembly of three block polymer micelles at solid interfaces is a good showcase for GIS from solid-liquid boundaries and a range of molecules has been investigated.…”
Section: Examplesmentioning
confidence: 94%
“…The ability to conduct novel experiments in this fi eld depends on instrumental developments. Major facilities around the world are actively developing instrumentation that is particularly useful for soft matter, such as off-specular neutron refl ection for studying polymer surfaces and interfaces 57,58 or grazingangle x-ray diffraction to study the reorganization of proteins in a Langmuir-Blodgett fi lm. 59 These approaches are both effective at interfaces, where the high intensities of nextgeneration sources are vital since the signal is intrinsically small.…”
Section: Scattering Approachesmentioning
confidence: 99%
“…Therefore, time-resolved NR measurements on the SOFIA reflectometer combined with the double-frame mode are useful to investigate the real-time evolution of non-equilibrium physical processes such as dewetting, interfacial diffusion above a glass transition temperature 39 and swelling behaviors of polymers contacting solvents or vapors. [6][7][8] In particular, SOFIA is expected to follow the kinetics at the soft interfaces on a time scale of seconds by time-resolved NR when J-PARC starts full-power operation in the near future to increase the neutron flux.…”
Section: Time-resolved Nr Measurement At Polymer Interfacementioning
confidence: 99%
“…Such time-resolved neutron reflectivity (NR) measurements have been attempted at overseas facilities to investigate the swelling behavior of polymers under solvent vapor, interfacial mutual mixing between hydrogenated (h-) and deuterated (d-) molecules, and dewetting behavior of polymers on solid surfaces. [6][7][8] In these experiments, it took 5-10 min to accumulate statistically sufficient reflected neutrons to generate NR plots, which implies that rapid structural changes within 5-10 min, if any have occurred, may not have been resolved. A shorter accumulation time is preferred to follow the diffusion and intermixing behavior of polymer chains at surfaces or interfaces.…”
Section: Introductionmentioning
confidence: 99%